2012
DOI: 10.1097/sla.0b013e31824f9dbf
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Procedure Rehearsal Is More Effective Than a Preoperative Generic Warm-Up for Endovascular Procedures

Abstract: Patient-specific simulated rehearsal of a CAS procedure significantly improves operative performance, compared to a generic VR warm-up or no warm-up. This technology requires further investigation with respect to improved outcomes on patients in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…The authors in one RCT [25] and one case study [26] reported that preoperative simulation shortens subsequent performance time in a simulated environment. In one crossover trial [27] and one case study [33] equivocal results were reported, with preoperative simulation reducing the time of some performance metrics, but not all. Finally, in only one RCT [24] did preoperative simulation not affect the time taken to perform simulated laparoscopic surgery.…”
Section: Studies Reporting Performance Timementioning
confidence: 99%
See 4 more Smart Citations
“…The authors in one RCT [25] and one case study [26] reported that preoperative simulation shortens subsequent performance time in a simulated environment. In one crossover trial [27] and one case study [33] equivocal results were reported, with preoperative simulation reducing the time of some performance metrics, but not all. Finally, in only one RCT [24] did preoperative simulation not affect the time taken to perform simulated laparoscopic surgery.…”
Section: Studies Reporting Performance Timementioning
confidence: 99%
“…Two cross-over trials [27,29] reported ambiguous findings for the effect of preoperative simulation on surgical performance; the first study [27] reported a significant effect as measured by one global rating scale, but no effect according to another also-reported scale. The second study [28] found a significant improvement in one assessed task, but not another.…”
Section: Studies Reporting Global Rating Scorementioning
confidence: 99%
See 3 more Smart Citations